2022
DOI: 10.1111/wvn.12589
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences and experiences of participation in surgical cancer care

Abstract: Patient participation is highly important for numerous reasons (World Health Organization, 2013); for example, it is associated with improved recovery, treatment outcomes, and rehabilitation (Arnetz et al., 2004), as well as increased motivation, better treatment outcomes, and greater satisfaction with the given care (Vahdat et al., 2014). Many countries, including Sweden, encourage patient participation by means of legislations and standards (Nolte et al., 2020). Yet, even if patient participation is advocated Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…What patients prioritise for their participation in IC is ‘being listened to’ (Item 1) and ‘having reciprocal communication’ (Item 3). Drott et al 45 also found that this was the case for surgical cancer patients, indicating the importance of constructive dialogues with HCPs. Any such dialogue should be two‐way to provide a mutual exchange of information and knowledge, including opportunities to address barriers such as reduced health literacy and/or fatigue 48 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…What patients prioritise for their participation in IC is ‘being listened to’ (Item 1) and ‘having reciprocal communication’ (Item 3). Drott et al 45 also found that this was the case for surgical cancer patients, indicating the importance of constructive dialogues with HCPs. Any such dialogue should be two‐way to provide a mutual exchange of information and knowledge, including opportunities to address barriers such as reduced health literacy and/or fatigue 48 .…”
Section: Discussionmentioning
confidence: 95%
“…Drott et al 45 also found that this was the case for surgical cancer patients, indicating the importance of constructive dialogues with…”
Section: Phase 2: Piloting Of the 4p Instrumentmentioning
confidence: 93%
See 2 more Smart Citations
“…Patient participation may increase motivation and quality of care. Having reciprocal communication, being listened to by the healthcare professional and learning about what was planned for the individual was an attribute of participation in a study of patients in surgical cancer care (72).…”
Section: Ii)mentioning
confidence: 99%